1987
DOI: 10.1093/carcin/8.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of radiation-induced transformation of C3H/10T½ cells by chymotrypsin inhibitor 1 from potatoes

Abstract: In this report, we have investigated whether a protease inhibitor obtained from potatoes (chymotrypsin inhibitor 1; CI-1) will inhibit carcinogen-induced transformation of C3H/10T1/2 cells. CI-1 was as effective as the soybean-derived Bowman Birk inhibitor at suppressing radiation-induced transformation of C3H/10T1/2 cells, at a concentration of 10 micrograms/ml. The inhibitor was not toxic to the cells at concentrations of 0.1-10 micrograms/ml, the concentrations of CI-1 employed in the transformation experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Proteinase inhibitors from plants have been known for some time to have anticarcinogenic properties (29) and potato Inh I had been shown to inhibit carcinogen-induced transformation of C3H͞10T 1 ⁄2 cells by x-irradiation (30). Inh I and Inh II were also found to be the most potent among several inhibitors of the formation of H 2 O 2 in polymorphonuclear leukocytes, activated by the tumor promoter 12-O-tetradecanoylphorbol 13-acetate (31).…”
Section: Resultsmentioning
confidence: 99%
“…Proteinase inhibitors from plants have been known for some time to have anticarcinogenic properties (29) and potato Inh I had been shown to inhibit carcinogen-induced transformation of C3H͞10T 1 ⁄2 cells by x-irradiation (30). Inh I and Inh II were also found to be the most potent among several inhibitors of the formation of H 2 O 2 in polymorphonuclear leukocytes, activated by the tumor promoter 12-O-tetradecanoylphorbol 13-acetate (31).…”
Section: Resultsmentioning
confidence: 99%
“…Animal tests and medical experiments have shown that proteinase inhibitors of certain types are anticarcinogenic (Yavelow et al, 1983;Troll et al, 1987;Troll & Kennedy, 1989;Kennedy, 1994;Liener, 1995). The anticarcinogenic properties include the ability to reduce oxygen-radical formation (Yavelow et al, 1982;, to suppress the growth of chemical-induced colon and anal gland tumours in rats (Billings et al, 1990), breast tumours in rats and humans (Troll et al, 1980;Tamir et al, 1990) and lung tumours in mice (Witschi & Kennedy, 1989), to suppress chemical-or radiation-induced cell transformation (Billings et al, 1987(Billings et al, , 1989 and to reduce spontaneous chromosome abnormality (Afzal et al, 1989). Epidemiological studies suggest that human populations which are known to have high concentration of certain proteinase inhibitors, mainly Bowman±Birk and Kunitz families, in their diet have lower rates of colon, breast, prostate and skin cancers (Correa, 1981;Kennedy, 1998;Chen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Gueven and coworkers [46] found a similar protective effect which was associated with the anti-chymotrypsin binding site of the protein. Other chymotrypsin inhibitors, including the chymotrypsin inhibitor I from potatoes, have been shown to be particularly effective in suppressing malignant transformation [47]. Because of the apparent association of the chymotrypsin inhibitory binding site with anti-carcinogenic properties, it has been hypothesised that chymotrypsin-like proteases are likely to be involved in carcinogenesis [48].…”
Section: Cancer Chemopreventive Propertiesmentioning
confidence: 99%